School Environment Analysis For Effective Learning - Mileandi Indra Regina; Muhibbin Syah; Bambang Samsul Arifin (al-Afkar, Journal For Islamic Studies, 2025)
An effective learning environment is a context where students can maximize their potential. In this environment, key elements such as interaction between teachers and students, the appropriate use of technology, supportive space design, and relevant curriculum play crucial roles. Skilled teachers who support active learning, motivate students, and build positive relationships can create an environment that fosters both intellectual and emotional growth.The use of technology is a significant component in modern learning environments. Proper integration of technology can enhance students' access to information, provide variation in teaching methods, and facilitate personalized and adaptive learning. Well-designed learning spaces also play a pivotal role. Ergonomic space design, utilization of open areas for collaboration, and provision of adequate resources can create an atmosphere that supports exploration and creativity. Moreover, a relevant curriculum aligned with current needs is also a key factor. A curriculum that blends theory with practical applications, considers the latest developments, and facilitates critical problem-solving can encourage meaningful learning. Overall, an effective learning environment is about creating a stimulating atmosphere that fosters curiosity, supports collaboration, and encourages critical thinking. When all these components are integrated effectively, students can reach their optimal potential in a nurturing and enjoyable learning environment.